ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH MELALUI ANALISIS RASIO KEUANGAN PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN TIMOR TENGAH SELATAN - Linus A. Ch Sakan (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2022)
This research was conducted at the Regional Financial and Asset Management Agency of South Central Timor Regency. The purpose of this study was to determine the financial performance of the Regional Government of Timor Tengah Selatan Regency for the 2015-2020 period based on the Regional Financial Independence Ratio, Effectiveness Ratio of Regional Original Revenue, Efficiency Ratio of Regional Original Income and Regional Expenditure Activity Ratio. This study uses a quantitative descriptive method with secondary data in the form of time series data on Financial Statements. The results of the study using the Regional Financial Independence Ratio showed that Regional Financial Independence obtained a very low criterion classification because it was in the interval below 25% and tended to decrease from year to year, the PAD Effectiveness Ratio showed the PAD Effectiveness obtained a very effective criteria classification because it was in the interfal in above 100% and tends to increase from year to year, the PAD Efficiency Ratio shows PAD Efficiency obtains a very efficient criteria classification because it is at an interval below 60% and tends to decrease from year to year and the Regional Expenditure Activity Ratio shows that Regional Expenditure Activities are prioritized on routine expenditures rather than capital expenditures and routine expenditures tend to decrease from year to year while capital expenditures tend to increase from year to year.